1969
DOI: 10.1149/1.2411841
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Electrooxidation of Dextrose in Neutral Media

Abstract: Electrooxidation of dextrose on platinized platinum electrodes has been studied in phosphate buffer at pH 7.4. Rest potentials are interpreted as mixed potentials. Galvanostatic curves have been observed to exhibit oscillatory voltage behavior. In the range of potentials investigated gluconic acid is observed as the reaction product and is found to inhibit oxidation of dextrose due to adsorption on the electrode surface. From the measurements of the adsorption characteristics of the acid, the oscillatory volta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
2

Year Published

1980
1980
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(53 citation statements)
references
References 1 publication
3
48
0
2
Order By: Relevance
“…21 Nevertheless, partial oxidation products of glucose irreversibly adsorb on and poison most electrocatalysts. 22 Hence, electrochemical assays of biological glucose solutions utilize glucose oxidation-catalyzing enzymes.…”
Section: Direct Nonenzymatic Electrooxidation and Electroreduction mentioning
confidence: 99%
“…21 Nevertheless, partial oxidation products of glucose irreversibly adsorb on and poison most electrocatalysts. 22 Hence, electrochemical assays of biological glucose solutions utilize glucose oxidation-catalyzing enzymes.…”
Section: Direct Nonenzymatic Electrooxidation and Electroreduction mentioning
confidence: 99%
“…Figure 3a shows the potential-time waveform of ASV. In the first step, Pt 3 PdNPs/RGO modified GCE was maintained at 0.67 V for 15 s. At this potential, high catalytically active PtO formed to electrooxidation the absorbents and generated a clean surface of the Pt 3 PdNPs/RGO when the potential was low enough to reduce the PtO formed [20]. Next, the potential was set to −0.45 V to concentrate glucose on the surface of the Pt 3 PdNPs/RGO.…”
Section: Electrocatalytic Oxidation and The Asv Detection Of Glucosementioning
confidence: 99%
“…At a potential lower than −0.3 V (vs a saturated calomel electrode), dehydrogenation of the glucose molecule at the hemiacetalic carbon 1 atom (C1) occurs, and adsorption of the glucose molecule onto the Pt surface follows. When the potential is positively moved forward, accompanied by the generation of catalytically active OH ads and subsequently PtO, catalytic oxidation of the absorbed glucose and the bulk glucose solution occur, and the two anodic oxidation current peaks are used to quantify the glucose concentration [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, there is no agreement in literature regarding the nature of the poisoning species [79]. Early studies indicated the reaction product gluconic acid [80] to be the poisoning species, whereas later works identified linear CO and bridged CO as adsorbates, depending on the pH [81,82].…”
Section: Factors Affecting Long-term Operationmentioning
confidence: 99%